DNA recognition by splicing variants of the Wilms' tumor suppressor, WT1. - Drummond, I A (1994)
The Wilms' tumor suppressor, WT1, is a zinc finger transcriptional regulator which exists as multiple forms owing to alternative mRNA splicing. The most abundant splicing variants contain a nine-nucleotide insertion encoding lysine, threonine, and serine (KTS) in the H-C link region between the third and fourth WT1 zinc fingers which disrupts binding to a previously defined WT1-EGR1 binding site. We have identified WT1[+KTS] binding sites in the insulin-like growth factor II gene and show that WT1[+KTS] represses transcription from the insulin-like growth factor II P3 promoter. The highest affinity WT1[+KTS] DNA binding sites included nucleotide contacts involving all four WT1 zinc fingers. We also found that different subsets of three WT1 zinc fingers could bind to distinct DNA recognition elements. A tumor-associated, WT1 finger 3 deletion mutant was shown to bind to juxtaposed nucleotide triplets for the remaining zinc fingers 1, 2, and 4. The characterization of novel WT1 DNA recognition elements adds a new level of complexity to the potential gene regulatory activity of WT1. The results also present the possibility that altered DNA recognition by the dominant WT1 zinc finger 3 deletion mutant may contribute to tumorigenesis.